K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

3 tháng 9 2020

Trả lời :

a, \(\frac{3}{4}-\left(\frac{1}{2}\div x+\frac{1}{2}\right)=\frac{3}{5}\)

=> \(\frac{1}{2}\div x+\frac{1}{2}=\frac{3}{20}\)

=> \(\frac{1}{2}\div x=\frac{-7}{20}\)

=> \(x=\frac{-10}{7}\)

b, (4 - x) . (2x + 3) = 0

=> \(\orbr{\begin{cases}4-x=0\\2x+3=0\end{cases}}\)

=> \(\orbr{\begin{cases}x=4\\x=\frac{-3}{2}\end{cases}}\)

c, \(\frac{4}{-3}=\frac{-12}{x}\)

=> 4x = 36

=> x = 9

d, \(\frac{4x}{-3}=\frac{12}{-x}\)

=> \(-4x^2=-36\)

=> 4x2 = 36

=> x2 = 9

=> x = \(\pm3\)

\(\text{a, 3(x+1)+4x=10}\)

\(\Rightarrow3x+3+4x=10\)

\(\Rightarrow7x+3=10\)

\(\Rightarrow7x=10-3=7\)

\(\Rightarrow x=1\)

c, x+1/10+x+2/9=x+3/8+x+4/7

=> (x+1/10 +1) +(x+2/9 +1)= ( x+3/8 +1) +(x+4/7 +1)

=> x+11/10 + x+11/9 = x+11/8 + x+11/7

...............

a) \(3\left(x+1\right)+4x=10\)

\(\Rightarrow3x+3+4x=10\)

\(\Rightarrow3x+4x=10-3\)

\(\Rightarrow7x=7\)

\(\Rightarrow x=7\)

a.Ta có: 2|x| + 3|1-x| - |x-3| =0

              2x + 3 - 3x - x +3  =0

              -2x + 6                   =0

              -2x                        =-6

                  x                        =3

b.Ta có:4|3x-1| + |x| - 2|x-5| +7|x-3| =12

             12x-4 + x -2(x-5) + 7x - 3 =12

             12x-4+ x - 2x +10 + 7x - 3=12

              18x + 3                            =12

              18x                                  =12-3

              18x                                  =9 

                 x                                   =1/2

1 tháng 8 2017

a. 2 |x |+ 3 | 1- x| - 5 | x - 3= 0

2 x + 3 - 3 x - x + 3 = 0

-2x + 6                    =  0

- 2 x                       = - 6

     x                       = 3

26 tháng 2 2018

a )  x + 5/12 = -2/3

=>  x = -2/3 - 5/12

=>  x = -8/12 - 5/12

=>  x = -13/12 

b ) 4/5 + 3/4 : x = 1/2

=>         3/4 : x  = 1/2 - 4/5

=>         3/4 : x  =   5/10 - 8/10

=>         3/4 : x  =     -3/10

=>                x   =     3/4 : -3/10

=>                x   =      -5/2 

c ) x/2 + x/3 = 1/4

=>   3x/6 + 2x/6   = 1/4

=>   ( 3x + 2x )/6  = 1/4

=>         5x/6        = 1/4

=>         20x/24     = 6/24

=>           20x        = 6

=>               x        = 6 : 20

=>               x        = 0 , 3

Chúc bạn học giỏi !!!